MiR‐122 decreases HCV entry into hepatocytes through binding to the 3′ UTR of OCLN mRNA. (28th October 2014) - Sendi, Hossein; Mehrab‐Mohseni, Marjan; Foureau, David M.; Ghosh, Sriparna; Walling, Tracy L.; Steuerwald, Nury; Zamor, Philippe J.; Kaplan, Keith J.; Jacobs, Carl; Ahrens, William A.; Russo, Mark W.; Clemens, Mark G.; et al.
Abstract Background & Aims Analysis in silico suggests that occludin (OCLN), a key receptor for HCV, is a candidate target of miR‐122; the most abundant hepatic micro RNA. We aimed to determine if miR‐122 can decrease HCV entry through binding to the 3′ UTR of OCLN mRNA. Design Huh7.5 cells were cotransfected with luciferase construct containing 3′ UTR of OCLN (pLuc‐OCLN) and with selected miRNAs (0–50 nM) and luciferase activity was measured. Huh7.5 cells were also infected by viral particles containing lenti‐miR122 genome or control virus. After 48 h, the cells were infected with HCV pseudo‐particles (HCVpp) and VSV pseudo‐particles (VSVpp). After 72 h of infection, luciferase activity was measured and HCVpp activity was normalized to VSVpp activity. Results miR‐122 binds to the 3′‐UTR of OCLN and down‐regulates its expression; cotransfection of miR‐122 mimic with pLuc‐OCLN resulted in a significant decrease in luciferase activity [by 55% (P < 0.01)], while a non‐specific miRNA and a mutant miR‐122 did not have any effect. miR‐122 mimic significantly down‐regulated [by 80% (P < 0.01)] OCLN protein in Huh7.5 cells. Accordingly, patients with chronic hepatitis C and higher levels of hepatic miR‐122 have lower hepatic expression of OCLN. Immuno‐fluorescence imaging showed a decrease in colocalization of OCLN and CLDN following miR‐122 over‐expression in HCV infected cells. Huh7.5 cells transiently expressing Lenti‐miR122 system showed 42% (P < 0.01) decrease in HCV entry. Conclusion This study uncovers a novel antiviral effect of miR‐122 on human liver cells and shows that over‐expression of miR‐122 can decrease HCV entry into hepatocytes through down‐regulation of OCLN.